2021
DOI: 10.5194/acp-21-2003-2021
|View full text |Cite
|
Sign up to set email alerts
|

Emission inventory of air pollutants and chemical speciation for specific anthropogenic sources based on local measurements in the Yangtze River Delta region, China

Abstract: Abstract. A high-resolution air pollutant emission inventory for the Yangtze River Delta (YRD) region was updated for 2017 using emission factors and chemical speciation based mainly on local measurements in this study. The inventory included 424 non-methane volatile organic compounds (NMVOCs) and 43 fine particulate matter (PM2.5) species from 259 specific sources. The total emissions of SO2, NOx, CO, NMVOCs, PM10, PM2.5, and NH3 in the YRD region in 2017 were 1552, 3235, 38 507, 4875, 3770, 1597, and 2467 Gg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 62 publications
(66 reference statements)
0
58
0
Order By: Relevance
“…Note that areas with the highest HCHO VCD in Shanghai did not appear in the city center (marked by the red box) but in the relatively remote Qingpu (QP) district, followed by Songjiang (SJ) and Jinshan (JS) district. Compared to the anthropogenic non-methane volatile organic compound (NMVOC) emissions, the distribution of HCHO VCDs does not show the same spatial pattern (An et al, 2021). The high HCHO in western Shanghai was frequently observed and may be explained by the transport of air masses containing high concentrations of reactive VOCs, sometimes from Zhejiang and Jiangsu provinces, and the significant contribution of local biogenic isoprene to HCHO (Su et al, 2019;Zhang et al, 2020Zhang et al, , 2021.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Note that areas with the highest HCHO VCD in Shanghai did not appear in the city center (marked by the red box) but in the relatively remote Qingpu (QP) district, followed by Songjiang (SJ) and Jinshan (JS) district. Compared to the anthropogenic non-methane volatile organic compound (NMVOC) emissions, the distribution of HCHO VCDs does not show the same spatial pattern (An et al, 2021). The high HCHO in western Shanghai was frequently observed and may be explained by the transport of air masses containing high concentrations of reactive VOCs, sometimes from Zhejiang and Jiangsu provinces, and the significant contribution of local biogenic isoprene to HCHO (Su et al, 2019;Zhang et al, 2020Zhang et al, , 2021.…”
Section: Resultsmentioning
confidence: 97%
“…Satellite remote sensing can achieve large-scale observation of atmospheric pollutant gases including HCHO, which has been widely used in recent years. Sensors currently available for HCHO observation include the Global Ozone Monitoring Experiment (GOME) on ERS-2 (Burrows et al, 1999;Martin et al, 2004b); Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) on ENVISAT (Bovensmann et al, 1999;Stavrakou et al, 2009); Ozone Monitoring Instrument (OMI) on Aura (Levelt et al, D. Li et al: OMI-observed HCHO and ozone sensitivity in Shanghai, China 2006;Zhu et al, 2017b); GOME-2 A, B, and C on METOP as the successor of GOME (Callies et al, 2000;De Smedt et al, 2012); Ozone Mapping and Profiler Suite (OMPS) on Suomi-NPP (Su et al, 2019); and Tropospheric Monitoring Instrument (TROPOMI) on Sentinel-5P (Veefkind et al, 2012;Vigouroux et al, 2020). OMI can provide daily data of HCHO with higher spatial resolution (13 km × 24 km).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in K + was the most pronounced, followed by Ca 2+ , Cl − , and EC. The annual decrease rates of K + , Ca 2+ , Cl−, and EC were 30.0%, 14.4%, 10.8%, and 9.5%, respectively, which was attributed to the nationwide control of fugitive dust, biomass burning, and coal combustion in the past few years (An et al, 2021;Cheng et al, 2019;Sun et al, 2013). Evident reduction of primary components in PM 2.5 may change the chemical characteristics of PM 2.5 .…”
Section: The 9-year Trends Of Pm 25 Nitrate and Related Speciesmentioning
confidence: 96%
“…Similar to POIS, the PIISs of O 3 in southwestern areas-including Lishui and Huangshan-is higher than in other areas, possibly due to downwind location and relatively low O 3 concentration in these areas. In addition, the neighboring cities of Hangzhou, Shaoxing, and Jinhua are high in O 3 , possibly due to their proximity to Hangzhou Bay, an area with sstrong emissions of VOCs and NOx (An et al, 2021).…”
Section: Regional O 3 and Pm 25 Transport Patterns In The Yrdmentioning
confidence: 99%